Periodontal conditions of teeth presenting pathologic migration. - Costa, Maurício Ribeiro; Silvério, Karina Gonzales; Rossa, Carlos Júnior; Cirelli, Joni Augusto [UNESP] (FapUNIFESP (SciELO), 2004)
The aim of the present study was to evaluate the periodontal conditions of anterior teeth that presented pathologic migration in patients with chronic periodontitis and to compare periodontal destruction in migrated versus non-migrated teeth. The sample included 32 patients of both sexes (mean age: 46.0 +/- 11.6 years) diagnosed with generalized chronic periodontitis and selected on the basis of the presence of pathologic migration in one or more anterior teeth. This migration was classified according to the following categories: facial flaring, diastema, proximal tilting, rotation or extrusion. The periodontal parameters recorded were clinical attachment loss (CAL) and percentage of radiographic bone loss (BL). Mean CAL of 5.50 +/- 2.20 mm and mean BL of 41.90 +/- 15.40% were found in 115 teeth assessed. The most frequent type of migration was facial flaring (34.80%), followed by diastema (27.00%). Extrusion was hardly observed in the sample (4.30%). However, greater severity of BL and CAL were observed in teeth with this type of migration (59.44% and 8.42 mm, respectively), and in teeth with facial flaring (45.17% of BL and 6.07 mm of CAL). Kruskal-Wallis test indicated that BL presented by teeth with extrusion or facial flaring was greater than that observed in rotated or tilted teeth (p < 0.05), while there was no difference between groups regarding CAL (p = 0.11). It was observed that anterior teeth with pathologic migration presented greater CAL and BL (5.1 mm and 40%) than non-migrated teeth (4.1 and 31%). The study indicated that the most prevalent kind of pathologic migration is facial flaring, which was associated to higher level of bone loss.
Keywords: Brazil; chronic disease; comparative study; female; human; male; middle aged; nonparametric test; osteolysis; pathology; periodontal disease; Alveolar Bone Loss; Chronic Disease; Female; Humans; Male; Middle Aged; Periodontal Attachment Loss; Statistics, Nonparametric; Tooth Migration